TINDAKAN ULTRA VIRES DIREKSI DAN AKIBAT HUKUMNYA BAGI PERSEROAN TERBATAS - Abdul Rokhim (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
The Actions of the Board of Directors are legally qualified as the actions of the Company as a legal entity if carried out by the authority and objectives of the Company as stated in the company's articles of association. The actions of directors that are carried out outside the authority or beyond the authority(ultra vires)cannot be qualified as the actions of the company. As a result, such legal action is not binding on the Company and only binds the Board of Directors personally with third parties. The problems examined are the limits of authority of the Board of Directors according to the UUPT and the doctrine and concept of ultra vires directors. Types of normative juridical research with conceptual approach and statute approach. The actions of the board of directors as long as it is carried out within the limits of the authority granted by the law and the articles of association of PT(intra vires)are legally viewed as the actions of PT as a legal entity. Actions of the Board of Directors that are carried out outside the authority or exceed their authority as stipulated in the laws and articles of association of PT(ultra vires)the Board of Directors must be personally responsible with third parties.